Penerapan User Centered Design (UCD) pada Website Hai Doc - Krishna Aryawan, Anak Agung Gde; Mahendra, Ida Bagus Made (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
This study aims to apply User Centered Design in the development of user interface design and user experience on the HaiDoc website. In website development, user interface and user experience (UI/UX) design is a very important initial stage in website creation. Then this UI/UX will provide an initial overview of a system that is created and provide an image for users to use and interact on this website. The UI/UX is designed on this website using a user centered design (UCD) approach. In user-centered design, there are 4 (four) stages in the UI/UX approach: analysis, planning, implementation, and testing. Users will be involved in evaluating the designs made, so the designs formed are expected to be by the users' wishes.